Export-Led Growth after COVID-19: The Case of Portugal - Wim Naudé; Martin Cameron (Institute of Labor Economics (IZA), 2020)
The COVID-19 pandemic has disrupted trade and global value chains. Small open economies such as Portugal are particularly vulnerable. In this paper we consider the impact of the pandemic on the country's exports, arguing that an export-led recovery is possible. The challenge is to identify viable export opportunities: one of the consequences of the COVID-19 pandemic is to have closed and shrunk export opportunities globally. Despite this we show that there are still significant under-utilized export opportunities for Portugal. We use the large UN-COMTRADE and CEPII BACI data sets to which we apply four sets of filters to identify 42,593 realistic export opportunities. These opportunities are worth exteuro286,6 billion in untapped revenue potential. The major markets for these products are countries such as United States, Germany, China, United Kingdom, France and Japan. We discuss the trade facilitation and industrial policy implications for utilizing these opportunities in the context of the relevant literature on trade and development.
Keywords: F17; F14; I15; L52; 330; COVID-19; trade; exports; international entrepreneurship; Portugal